Concurrency Control in Distributed System Using Mutual Exclusion - Kanrar, Sukhendu; Chaki, Nabendu; Chattopadhyay, Samiran; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book presents various state-of-the-art approaches for process synchronization in a distributed environment. The range of algorithms discussed in the book starts from token based mutual exclusion algorithms that work on tree based topology. Then there are interesting solutions for more flexible logical topology like a directed graph, with or without cycle. In a completely different approach, one of the chapters presents two recent voting-based DME algorithms. All DME algorithms presented in the book aim to ensure fairness in terms of first come first serve (FCFS) order among equal priority processes. At the same time, the solutions consider the priority of the requesting processes and allocate resource for the earliest request when no such request from a higher priority process is pending.
Preface -- Introduction -- State of the Art Review -- Tree Based Mutual Exclusion.-A Graph-based Mutual Exclusion Algorithms using Tokens -- Voting-based Mutual Exclusion Algorithms -- Conclusions -- References. .
Keywords: Telecommunication; Algorithms; Control engineering; Computer networks .; Communications Engineering, Networks; Algorithms; Control and Systems Theory; Computer Communication Networks